From ephphatha to deaf pastors : deaf pastoral ministry - Broesterhuizen, Marcel (Louvain theological & pastoral monographs, 2019)
In the past, pastoral care with the deaf generally took place from the care perspective of hearing pastors: deafness as a disability that deserved charity and a missionary effort towards integration of deaf people into a hearing society. This book proposes a liberatory pastoral model that starts from deaf people's self-experience, Deaf Cultures, and Sign Language as deaf people's most natural language: deafness as a way of life. In a deaf way of life, deafness is not an impairment or disability, but a world in its own worth. In this Deaf World deaf people are not passive receivers of pastoral ministry, but its primary agents. Topics treated in this book are: the history of deafness in Western culture, deaf people's self-experience, a non-dichotomizing view on "impairment," a theological view on language, the deaf community as locus theologicus, and Bible translation into Sign Language